Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1093/ejechocard/jer136
|View full text |Cite
|
Sign up to set email alerts
|

Adverse effect of right ventricular pacing prevented by biventricular pacing during long-term follow-up: a randomized comparison

Abstract: www.clinicaltrials.gov (identification number: NCT00228241).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 13 publications
0
23
0
4
Order By: Relevance
“…In the RV pacing group, LVEF progressively decreased over time from the first to the second year of follow‐up, but it remained unchanged in the CRT group, leading to a significant difference of 9.9 percentage points between groups at 2‐year follow‐up (P < 0.001). Similarly, Albertsen et al 31 randomized 50 patients with normal cardiac function to RV pacing or CRT. LVEF differed significantly between the two groups during 3 years of pacing (P = 0.003).…”
Section: Effects Of Rv Pacing In Chronic Av Block In the Absence Of Bmentioning
confidence: 99%
See 1 more Smart Citation
“…In the RV pacing group, LVEF progressively decreased over time from the first to the second year of follow‐up, but it remained unchanged in the CRT group, leading to a significant difference of 9.9 percentage points between groups at 2‐year follow‐up (P < 0.001). Similarly, Albertsen et al 31 randomized 50 patients with normal cardiac function to RV pacing or CRT. LVEF differed significantly between the two groups during 3 years of pacing (P = 0.003).…”
Section: Effects Of Rv Pacing In Chronic Av Block In the Absence Of Bmentioning
confidence: 99%
“…A baseline LVEF cut‐off value has not yet been clearly defined 32,33 . Based on data from some studies involving patients with AV junction ablation for AFib and also patients with standard indication for pacing, chronic RV pacing can induce a reduction in LVEF of 5–10 percentage points, depending on baseline characteristics and time to evaluation after implantation 24–26,28–31 (Table II). Therefore, a baseline LVEF cut‐off value of 40–45% should be discussed as a criterion for a CRT device in patients in whom RV pacing cannot be avoided.…”
Section: Effects Of Rv Pacing In Chronic Av Block In the Absence Of Bmentioning
confidence: 99%
“…We included 10 studies, of which three had additional reports with long‐term follow‐up results. Six studies compared BiVP and RVP, 11,13‐19 and four compared HBP and RVP 3,4,20‐22 . Figure 1 summarizes the search strategy.…”
Section: Resultsmentioning
confidence: 99%
“…To avoid potential double counting of subjects, we excluded 4 studies that reported results for the same trial populations. Eight studies comprised the final analysis, 4 comparing BiVP versus RVP (N5438) [28][29][30][31] and 4 evaluated HisBP versus RVP (N5241) 25,[32][33][34] (Figure 2). The characteristics of the studies are summarized in Data Supplements 5 and 6.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies reported the impact of BiVP on 6minute walk distances and detected no significant difference with BiVP (MD: 6.736 m; 95% CI: -2.82 to 16.29 m; p50.167; I 2 5 0%). [28][29][30] Two of the studies observed no significant improvement in 6-minute walk distances. 28,30 The third study, which evaluated patients with chronic atrial fibrillation (AF) who underwent atrioventricular node ablation, found that at 6 months there was a significant improvement with both RV or BiVP but that BiVP resulted in a greater improvement in 6-minute walk distance (61.2690 m versus 82.9694.7 m; p50.04).…”
Section: Bivp Versus Rvpmentioning
confidence: 92%